Konstruksi Identitas Korban dan Pelaku Pemerkosaan di Media Online Detik.com - Aprilia, Elen Nur; Jannah, Raudlatul (University of Jember)
Abstract The media can influence the public mindset. Similarly, the news of rape informed by detik.com online media can affect the public mindset towards rape. Meanwhile, news conveyed by media is the construction result of reality which also cannot be separated from reporters’ subjectivity. How Detik.com online media represents the rape victims and doers in its reporting will affect the way the community members view the rape victims and perpetrators. This research was aimed to identify the identity construction of rape victims and perpetrators on Detik.com online media. The method used in this research was critical discourse analysis by Norman Fairclough. In the critical discourse analysis of Norman Fairclough, the research was conducted only at the text level covering representation, relation and identity. The research results showed that there were two patterns of rape; that is, those committed by family members and those by non-family members. Media construction on the victims, among others, karaoke girl guide, victim lover, female victims with disability, grandmother raped by younger man, poor girl, facebook friends, vegetable seller, public transportation passenger, housewife, victim’s friend, victim's neighbor. Based on all of the identity constructions, the media dominantly still blamed women for causing the rape to occur.